The evolution of the Journal of Applied Oral Science: a bibliometric analysis (Journal of Applied Oral Science, 2008)
The purpose of this study was to make a brief diagnosis of the evolution of the Journal of Applied Oral Science (JAOS) between 2005 and 2007, by reviewing quantitative and qualitative aspects of the articles published in the JAOS within this period. All articles published in the JAOS in the time span established for this survey were analyzed retrospectively and a discussion was undertaken on the data referring to the main bibliometric indexes of production, authorship, bibliographic sources of the published articles, and the most frequently cited scientific journals in the main dental research fields. A total of 247 papers authored and co-authored by 1,139 contributors were reviewed, most of them being original research articles. The number of authors per article was 4.61 on the average. Regarding the geographic distribution, the authors represented almost all of the Brazilian States. Most published articles belonged to the following dental research fields: Endodontics, Restorative Dentistry, Dental Materials and Prosthodontics. The ranking of the most frequently cited scientific journals included the most reputable publications in these dental research fields. In conclusion, between 2005 and 2007, the JAOS either maintained or improved considerably its bibliometric indexes. The analysis of the data retrieved in this study allowed evaluating the journal's current management strategies, and identifying important issues that will help outlining the future directions for the internationalization of this journal.